Optimizing the Arts and Culture of the Young Generation of Kandangan Village - Nirmala, Luvitha Eka; Tias, Evi Wahyuning; Udin, Yus Safik; Salsabila, Qonitah; Meilan, Ria (IMPOWERMENT SOCIETY, 2025)
Kandangan Village, known for its rich cultural heritage, faces challenges in preserving traditions and fostering youth entrepreneurship. The Student Organization Capacity Strengthening Program (PPK Ormawa) was implemented to increase cultural awareness, develop cultural infrastructure, and empower the younger generation through arts-based businesses. The program includes traditional arts and entrepreneurship training, digital marketing promotion, and the establishment of the Tengger Brang Wetan Cultural Museum. The museum serves as an educational center and tourist attraction, showcasing local arts, crafts, and oral traditions. As a result, community participation in cultural activities increased, leading to the creation of youth-led businesses in handicrafts, culinary arts and cultural tourism. Digital platforms also helped increase public engagement and tourism. The findings highlight the importance of cultural preservation as an economic driver, demonstrating that participatory approaches can sustain local heritage while promoting economic growth in rural communities.